Pengaruh Total Utang, Modal Kerja, dan Biaya Operasional Terhadap Laba Bersih Pada Perusahaan Sektor Farmasi Di Bursa Efek Indonesia Tahun 2020-2024 - Yobel Gabriel Sitanggang; Sucitra Dewi; Indah Cahya Sagala (Prodi Bisnis Digital Universitas Pahlawan Tuanku Tambusai, 2026)
The purpose of this study is to determine the effect of total debt, working capital, and operating costs on net profit in pharmaceutical companies listed on the Indonesia Stock Exchange for the 2020-2024 period. The research design used an associative approach. The population in this study was 11 pharmaceutical companies listed on the Indonesia Stock Exchange for the 2020-2024 period. The sampling technique used was purposive sampling, resulting in a total of 11 pharmaceutical companies listed on the Indonesia Stock Exchange for the 2020-2024 period. The type of data used in this study is quantitative. The data source used in this study was obtained from the Indonesia Stock Exchange (IDX) website. The data analysis method used multiple linear regression analysis with SPSS.25. Based on the results of the t-test, it can be concluded that total debt has a no effect on net profit, working capital has a positive and significant effect on net profit, and operating costs have a positive and significant effect on net profit. Based on the f-test results, it was concluded that total debt, working capital, and operating costs simultaneously influenced net profit in pharmaceutical companies listed on the Indonesia Stock Exchange in 2020-2024.